Dam disruption in international scientific literature: A bibliometric analysis (Research, Society and Development, 2021)
The breaking of dams is a topic that has recently gained prominence in the media, mainly due to major disasters involving loss of human lives. A bibliometric analysis of the topic is opportune so that studies with a scientific basis can be systematized to support safety measures and prevention of this type of accident. In this sense, this work analyzed the international scientific production on the rupture of dams through a quantitative approach that aimed to measure the bibliometric dynamics of the theme in the period between the years 1945 and the beginning of 2021. A survey was carried out in the main collection of the database. interdisciplinary data Web of Science considering as main criteria the aforementioned time frame and the occurrence of the keyword “Dam Break” in the title of the publications. We only searched for the article modality, published in the English language. The survey metadata was downloaded in Excel spreadsheet format and descriptive statistics were applied to classify and quantify the information. The results show that the occurrence of the theme in the international literature only occurs from the year 1980, with the Journal of Hydraulic Research as the main vehicle of communication, and the main country of origin, China. The total number of publications found was 306 articles, 44 of which were considered to have the greatest impact in the scientific literature, according to the H-index. It is concluded that the researched theme has been growing in importance in recent years with the increase in the number of publications, mainly in the areas of Water Resources and Civil Engineering, since 2006.